Diffuse synovial hemangioma of the knee: a case report - Yilmaz, Erhan; Karakurt, Lokman; Ozdemir, Hüseyin; Serin, Erhan; Incesu, Mustafa (My University, 2004)
Synovial hemangioma is a rare benign tumor of joint cavities. It may be a cause of pain and recurrent joint swelling in children and young adults. Diffuse synovial hemangioma was diagnosed in a 25-year-old male patient with complaints of right knee pain and swelling of a 10-year history. Direct radiography, venography, magnetic resonance imaging, and diagnostic arthroscopy enabled the diagnosis. Surgical excision was not considered because of diffuse involvement and many pigmented areas in the skin; instead, the patient was monitored conservatively. At the end of a year, the severity of complaints and the size of the lesion did not increase. Since there is a high risk for recurrence following open synovectomy for diffuse synovial hemangiomas, conservative treatment may be an alternative approach in selected cases.
Dizde yaygin sinovyal hemanjiyom: Olgu sunumu.
Keywords: Adult; Arthroscopy; Diagnosis, Differential; Hemangioma; Humans; Knee Joint; Magnetic Resonance Imaging; Male; Soft Tissue Neoplasms; Synovial Membrane; adult; arthroscopy; article; case report; differential diagnosis; hemangioma; human; knee; male; nuclear magnetic resonance imaging; pathology; radiography; soft tissue tumor; synovium